Assessment of Water, Sanitation, and Hygiene (WASH) practices in Onitsha Urban Area of Anambra state, Nigeria - Nwoye, Theresa Nwakaego; Ezenwaji, Emeka Emmanuel (Humanities Horizon, 2025)
Water, Sanitation, and Hygiene (WASH) are essential components of public health, particularly in urban areas facing rapid population growth and infrastructural challenges. Inadequate WASH services contribute significantly to the burden of disease, environmental degradation, and overall poor quality of life. The study adopted a mixed-method research design to assess integrated Water, Sanitation, and Hygiene (WASH) practices in Onitsha Urban Area, Anambra State, Nigeria. Onitsha, a major commercial hub, experiences rapid urbanization and infrastructural strain. The study area’s geography, population growth, climate, geology, and economic activities were considered in evaluating WASH services. A sample of 400 residents from Federal Housing Estate was selected using Taro Yamane’s formula. Data were collected via structured questionnaires and field inspections, with instrument reliability confirmed through a pilot study. Analysis involved two-way ANOVA and Principal Component Analysis to identify key factors contributing to poor WASH conditions. Based on the findings, the demographic analysis of (400) respondents showed age distribution as follows: (17%) were 18–28, (28%) aged 29–39, (36%) aged 40–50, and (19%) above 50. Educationally, (8%) had no formal education, (20%) completed primary, (48%) had secondary, and (24%) attained tertiary education. Ethnic composition was largely Igbo at (90.15%), followed by Hausa (3%), Yoruba (1.85%), and others (5%). Household sizes showed (38%) had 1–3 children, (42%) had 4–6, (16%) had 7–9, and (4%) had more than 9. WASH practices revealed strong agreement on clean water prioritization, handwashing, and sanitation, while disagreements emerged on issues like pipe expansion and sustainable water systems. The study highlights the need for integrated policy action, community sensitization, and investment in WASH infrastructure to improve public health outcomes in Onitsha.